2006
DOI: 10.1577/t05-233.1
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Streamflow Lowers Dry‐Season Growth of Rainbow Trout in a Small Stream

Abstract: A wide variety of resource management activities can affect surface discharge in small streams. Often, the effects of variation in streamflow on fish survival and growth can be difficult to estimate because of possible confounding with the effects of other variables, such as water temperature and fish density. We measured the effect of streamflow on survival and growth of rainbow trout Oncorhynchus mykiss in a small stream in northwestern California by manipulating the flow entering four of eight enclosed stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
154
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(168 citation statements)
references
References 24 publications
11
154
3
Order By: Relevance
“…Larger residents require more space and tend to occupy faster and deeper water than smaller individuals, and streams that do not maintain sufficient flow are unlikely to support large, old, resident O. mykiss (Todd et al 2008). As an example, by manipulating stream flow, Harvey et al (2006) found that growth rates of O. mykiss were 8.5 times lower in reaches with reduced flow than in control reaches. This line of reasoning has led to the hypothesis that higher summer flows improve opportunities for feeding and development, thereby permitting the expression of larger and older freshwater residents ( Fig.…”
Section: Stream Flowmentioning
confidence: 99%
“…Larger residents require more space and tend to occupy faster and deeper water than smaller individuals, and streams that do not maintain sufficient flow are unlikely to support large, old, resident O. mykiss (Todd et al 2008). As an example, by manipulating stream flow, Harvey et al (2006) found that growth rates of O. mykiss were 8.5 times lower in reaches with reduced flow than in control reaches. This line of reasoning has led to the hypothesis that higher summer flows improve opportunities for feeding and development, thereby permitting the expression of larger and older freshwater residents ( Fig.…”
Section: Stream Flowmentioning
confidence: 99%
“…First, the time scale over which flow is reduced may be a critical determinant of whether behavioural drift increases. For instance, several studies have observed decreased drift flux and concentration across natural declines in flow (Leeseberg and Keeley 2014) or experimental declines over multiple weeks (Harvey et al 2006;Wooster et al 2016). Second, there is some evidence that taxa may respond in different directions to flow declines (James et al 2009;Kennedy et al 2014).…”
Section: Hydraulic Effects On Drift Fluxmentioning
confidence: 99%
“…These changes in the riverine and floodplain environments in turn have important impacts on river biota. Water abstraction can influence fish assemblage composition (Benejam et al, 2010) and the density and growth rates of sensitive fish (e.g., salmonids, Harvey et al, 2006;Lange et al, 2014). Water abstraction also has important impacts on benthic invertebrate assemblages.…”
Section: Introductionmentioning
confidence: 99%